Concentration‐dependent frequency shifts of the CS stretching modes in ethylene trithiocarbonate studied by Raman spectroscopy. (6th April 2015) - Wu, Fengqi; Wang, Huigang; Zheng, Xuming
<x xml:space="preserve">Abstract</x> Resonant with the CS π → π* electronic transition, the intensity of CS stretching and its overtone have been greatly enhanced in the 488‐ and 319‐nm excited resonance Raman spectra. The isotropic and anisotropic parts of the Raman spectra of CS stretching modes of ethylene trithiocarbonate (ET) at different concentrations have been analyzed in order to study the noncoincidence effect (NCE). In neat ET, the experimentally measured values of noncoincidence Δυnc are 4.60 cm−1 for the CS stretching modes, which reduce to 1.30 cm−1 at the mole fraction χm (ET) = 0.13. Both the isotropic and anisotropic peak frequencies of CS stretching were found to shift to higher wavenumber when the concentrations are diluted, while the value of Δυnc goes on decreasing upon dilution. The absolute Raman cross section of carbonyl stretching was also measured, and their behavior was unusual (first increasing and then decreasing with the decrease of concentration). The experimental result shows that there may exist self‐association in the high concentration, and the main NCE mechanism may be due to the transition dipole–transition dipole coupling between the ET molecules. Copyright © 2015 John Wiley & Sons, Ltd.